2017
DOI: 10.1590/1980-85852503880004908
|View full text |Cite
|
Sign up to set email alerts
|

Os efeitos da crise económica na situação laboral dos imigrantes: o caso dos brasileiros em Portugal

Abstract: Resumo. Após um período de crescimento económico que potenciou o aumento dos fluxos migratórios para Portugal, o país entrou, após 2008, numa forte crise económica com impactos muito negativos no emprego e em sectores que empregavam um grande número de imigrantes como a construção civil. Pela incorporação diferenciada dos imigrantes nos vários segmentos do mercado de trabalho é importante analisar em profundidade a extensão e a abrangência destes efeitos, designadamente tendo em conta a origem geográfica dos i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Although the difference between living standards in Brazil and Portugal has already been reported in studies that look at the population in general (Pnud, 2019;Oliveira et al, 2017;Pereira & Esteves, 2017), the results of this study are of great use, considering changes to the social security system in both countries that include raising the retirement age, as well as the discussion about the factors that make up satisfaction in retirement. Because retirement is a special time of life, with its own set of motivations, needs, preferences and experiences, it is crucial that settings provide decent living conditions and opportunities to foster well-being (Santos et al, 2018).…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…Although the difference between living standards in Brazil and Portugal has already been reported in studies that look at the population in general (Pnud, 2019;Oliveira et al, 2017;Pereira & Esteves, 2017), the results of this study are of great use, considering changes to the social security system in both countries that include raising the retirement age, as well as the discussion about the factors that make up satisfaction in retirement. Because retirement is a special time of life, with its own set of motivations, needs, preferences and experiences, it is crucial that settings provide decent living conditions and opportunities to foster well-being (Santos et al, 2018).…”
Section: Resultsmentioning
confidence: 60%
“…Data from the Organization for Economic Cooperation and Development (Organization for Economic Cooperation and Development, 2017) indicate that the average earnings of Portuguese workers are more than twice the earnings of Brazilian workers, whether formally or informally employed, in various sectors. These differences can be confirmed by the increase in the migratory flow of Brazilians to Portugal, especially after the economic crisis of 2008, which had negative impacts on employment (Pereira & Esteves, 2017) migrants seeking better living conditions, especially in health care (Oliveira et al, 2017;SEF, 2017). The results of this research allow us to advance the study of well-being in retirement with regard to the similarities and differences in perception of satisfaction among retirees in different contexts.…”
Section: Resultsmentioning
confidence: 99%
“…Portugal’s adverse period of austerity (2011–15) in the aftermath of the 2008 financial crisis slowed this migration cycle. Brazilian arrivals contracted and the number of residents decreased by 30% in that period (Pereira and Esteves, 2017; SEF, 2017). 2…”
Section: Brazilians In Portugalmentioning
confidence: 99%
“…Although Portugal is an important destination for Brazilians and there is recent academic production present in the main repositories of national articles (CAPES, Scielo Brasil, among others), there are many articles that treat the topic superficially (for example, Ferreira, 2017;Guedes & Marques, 2008;Iorio & Nogueira, 2019;Oro, 2017;Pereira & Esteves, 2017;Roberto & Moleiro, 2015;Saturnino, 2015;Vala, Brito, & Lopes, 2015), especially with aspects relative to entrepreneurship of Brazilian immigrants in Portugal.…”
Section: Introductionmentioning
confidence: 99%
“…In recent academic literature, several other studies of Brazilians in Portugal are reported. The themes vary, ranging from the international mobility of students and young people to Portugal (Fonseca, Esteves, & Iorio, 2015;Fonseca, Pereira, & Iorio, 2016;Iorio & Nogueira, 2019;Togni, 2015), the effects of the crisis and labor issues of Brazilian immigrants in Portugal (Pereira & Esteves, 2017), the adaptation of Brazilian expatriates in the country and the resilience processes of immigrants (Ferreira, 2017;Roberto & Moleiro, 2015). Brazilian immigration to Portugal can generate an imaginary of both the Portuguese about Brazilians and the reverse (Lisboa, 2016); however, we know that there are many expressions of racism in Portugal (Vala et al, 2015).…”
mentioning
confidence: 99%